Binder-free in situ interface reconstruction of NiMoO4 nanorods over Ni(OH)2 nanosheets for efficient urea oxidation - Kumar, Yogesh; Barik, Sidharth; Kharabe, Geeta Pandurang; Torris, Arun; Singh, Mayank U.; Mohan, S.; Galave, Chaitanya; Tekawadia, Jyoti; Kanawade, Rajesh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Replacing the energy-intensive oxygen evolution reaction (OER) with the urea oxidation reaction (UOR) in electrochemical water splitting offers simultaneous green hydrogen production and urea-rich wastewater oxidation, enhancing energy efficiency and economic viability. In this study, a non-noble metal-based binder-free NiMoO4/Ni(OH)2/NF electrocatalyst is developed, featuring NiMoO4 nanorods anchored on Ni(OH)2 nanosheets. This unique morphology facilitates a highly active in situ reconstructed interface, delivering a current density of 134 mA cm-2 at 1.40 V (vs RHE) in 1 m KOH with 0.33 m urea, significantly outperforming its individual components. The catalyst demonstrates excellent stability over 50 h at 30 mA cm-2. When integrated into an anion exchange membrane urea electrolyser (13 cm2 area) with Pt@C/NF as the HER cathode, the system achieves 192 mA cm-2 at 1.60 V. The post-UOR studies confirm the presence of an amorphous NiMoO4-crystalline Ni(OH)2 interface, which plays a key role in enhancing the availability of the active sites to enhance the UOR performance. The improved electrochemical performance of the engineered catalyst can be ascribed to the in situ reconstructed amorphous-crystalline interface, optimal hydrophilicity, reduced charge transfer resistance, and the distinct morphology. This strategy offers a promising pathway for developing highly active electrocatalysts for energy conversion applications.
Keywords: AEM; electrolyser; OWS; tomography; UOR; wastewater

Optimisation of metallic bismuth nanoparticle supported Pt-Bi(x%)/C hybrid electrocatalyst for cost effective and efficient hydrogen production in alkaline media - Dokhe, Revati; Ugale, Atul; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (International Journal of Hydrogen Energy, 2025)
The present study employed a simple mechanochemical method followed by 24-h ultrasonication to synthesize oxide-free metallic bismuth (Bi) nanoparticles. This was further used to synthesize a Pt-Bi(x%)/C (NC-x) hybrid electrocatalyst for the hydrogen evolution reaction in alkaline media. X-ray photoelectron spectroscopy and contact angle measurements reveal, Bi modifies the electronic structure and surface morphology of the Pt/C electrocatalyst, thus enhancing reaction kinetics and active site availability. The relative three-electrode study reveals that optimised NC-20 electrocatalyst reduces the overpotentials by 10.44 % and enhances the current density by 53 % compared to commercial Pt/C. The practical applicability of the NC-20 electrocatalyst was studied with the 13 cm2 single cell anion exchange membrane electrolyser. The catalyst demonstrates promising performance where the current density of NC-20//IrO2 relatively increases by 22.6 % compared to standard Pt/ C//IrO2, and shows continuous production and stable performance when monitored for 30 h.
Keywords: AEM; Bismuth nanoparticles; electrocatalyst; Full cell electrolysis; hydrogen evolution reaction; water electrolysis